The Balustrade and the ‘kekisi’: A strategy in infusing Malay identity through filters and railings in South East Asian urbanism and architecture - Norzalifa Zainal Abidin; Puteri Shireen Jahn Kassim; Zumahiran Kamaruddin (Universitas Indraprasta PGRI, 2019)
Fundamentally, the element of the Malay decorative kekisi is either as a perforation between inside and outside or separation between two functional spaces are endemic in the traditional world. The same functions can be re-engaged in the modern world, to encourage good airflow and natural ventilation, rather than fully dependent on air conditioning. The paper discusses how the element itself reflects a fusion and unity of both form and function. It has sustainable and climatic functions and also has versatile elements which can be inserted to infuse identity consciousness and expressions in a range of scale of spaces, construction elements and forms. In this paper, the generic elements and their cultural variations are highlighted in the traditional building of Melaka and Kedah in Malaysia.